2020
DOI: 10.1128/jvi.01847-19
|View full text |Cite|
|
Sign up to set email alerts
|

β-Catenin Is Required for the cGAS/STING Signaling Pathway but Antagonized by the Herpes Simplex Virus 1 US3 Protein

Abstract: The cGAS/STING-mediated DNA-sensing signaling pathway is crucial for interferon (IFN) production and host antiviral responses. Herpes simplex virus I (HSV-1) is a DNA virus that has evolved multiple strategies to evade host immune responses. Here, we demonstrate that the highly conserved β-catenin protein in the Wnt signaling pathway is an important factor to enhance the transcription of type I interferon (IFN-I) in the cGAS/STING signaling pathway, and the production of IFN-I mediated by β-catenin was antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Alternatively, activation of TBK1 by STING can activate the NF-κB pathway [ 79 ] ( Figure 1 ). Recently, it has been shown that β-catenin is an essential component of the cGAS-STING pathway and blocking the nuclear translocation of β-catenin reduces type I IFN production [ 80 ]. While cGAS is primarily cytoplasmic, it is partially located in the nucleus of fibroblasts and keratinocytes and there is evidence it plays a role in stabilizing IFI16, another viral DNA sensor (described below) [ 81 , 82 ].…”
Section: Recognition Of Hsv-1 By the Innate Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, activation of TBK1 by STING can activate the NF-κB pathway [ 79 ] ( Figure 1 ). Recently, it has been shown that β-catenin is an essential component of the cGAS-STING pathway and blocking the nuclear translocation of β-catenin reduces type I IFN production [ 80 ]. While cGAS is primarily cytoplasmic, it is partially located in the nucleus of fibroblasts and keratinocytes and there is evidence it plays a role in stabilizing IFI16, another viral DNA sensor (described below) [ 81 , 82 ].…”
Section: Recognition Of Hsv-1 By the Innate Immune Systemmentioning
confidence: 99%
“…pUS3, in conjunction with pUL13 also dampens the IFNγ response by inhibiting the phosphorylation of IFNGR1, a requirement for complete activation of the IFNGR receptor [ 203 ]. Recent evidence has shown that pUS3 also inhibits the actions of β-catenin following activation of the cGAS-STING pathway by blocking the nuclear translocation of β-catenin in mouse fibroblasts, further dampening the type I IFN response [ 80 ].…”
Section: Hsv-1 Evasion Response Against the Innate Immune Systemmentioning
confidence: 99%
“…The culture for HepG2, Huh7, and HEK293T cells was followed as described [ 26 28 ]. According to the manual, the cells were transfected with target plasmids with LipoMax DNA transfection reagent.…”
Section: Methodsmentioning
confidence: 99%
“…At the moment, the cross talk that may exist between GSK-3/β-catenin pathways and the effectors described above were documented at the level of the recruitment of GSK-3 to TBK1 in herpes simplex virus (HSV-1)-infected cells [76]. Recently, the requirement of β-catenin in the cGAS/STING mediated activation of the IFN pathway was shown in a reporter assay [119]. This could likely happen through the binding of p-β-catenin Ser552 with IRF3 promoter in association with TCF4, as reported following STING activation in Toxoplasma gondii infection [120].…”
Section: Cytosolic Dna Sensorsmentioning
confidence: 99%
“…This could likely happen through the binding of p-β-catenin Ser552 with IRF3 promoter in association with TCF4, as reported following STING activation in Toxoplasma gondii infection [120]. It is interesting to note, however, that viral interference inhibiting the functions of both GSK-3 and β-catenin has been observed with many DNA viruses-encoded proteins including the hepatitis B virus (HBV) X protein [121], the Epstein-Barr virus (EBV) LMP2A [122,123], the latency-associated nuclear antigen of Kaposi's sarcoma-associated herpesvirus (KSHV) [124], and the US3 protein from HSV-1 [119]. In addition to viral interference antagonizing the GSK-3/β-catenin pathways, other DNA viruses, such as human cytomegalovirus, use GSK-3 at their advantage to induce the degradation of SPOC1 (survival time-associated PHD (plant homeodomain) finger protein in ovarian cancer 1), a transcriptional coregulator involved in the inhibition of viral immediate-early (IE) gene expression [125].…”
Section: Cytosolic Dna Sensorsmentioning
confidence: 99%